Utilization of Cocoa Bean Husk Extract (Theobroma cacao L) on The Product Chocolate Cookies - Jumriah langkong; Meta Mahendradatta; Mulyati M. Tahir; Andi Nur Faidah Rahman; Nurlaila Abdullah; N Marina (jurnal1, 2020)
Cocoa bean husk is one of the byproducts of cocoa, which is only utilized as animal feed and low economic value. The economic value of cocoa bean husks can be enhanced by extracting the husk using methanol into a powder and applied to a product into cookies. Cookies are types of biscuit which are made from soft dough, high in fat and relatively crisp. The purpose of this study is to know the amount of powder that is added and its impact on the cookies product. The analysis was done for the sensory test. In the organoleptic test, the color and odor which were preferred by the panelists was treatment A0 (control), whereas the taste and texture were treatment A1 (addition of 5% powder).